Muslim consumers' awareness and perception of halal food fraud - Ruslan, Akma Aizatul Ain (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
Halal is an important aspect of food selection as it is one’s part to obey religious obligations and commandments. Since the halal food industry covers the farm-to-table operations, therefore unwanted practices which culminate to halal food fraud along food supply chain has become a major concern among Muslim consumers. This is because food fraud is a subjective concept, hence objective verification of fraudulent activities and the extent of fraud could be difficult to verify. The current study was therefore carried out to determine Muslim consumers’ awareness and perceptions towards halal food fraud. A total of 352 respondents from Klang Valley areas were randomly selected to be the target respondents in this study. The data obtained were analyzed using descriptive analysis, chi-square analysis, and factor analysis. The results indicated that most of the respondents (96.9%) in Klang Valley areas were aware of halal food fraud issues. The findings also showed that gender, age, education level, and occupation had significant relationships with awareness of halal food fraud. Three factors were classified as influential to Muslim consumers’ perception towards halal food fraud namely halal logo, labeling and packaging, authorities’ exposure and enforcement as well as consumer attitude. The study recommended that Islamic authorities should continuously seek ways to improve and educate consumers towards halal food fraud while the government should further strengthen their important role of enforcing law and penalties to irresponsible industry players.